Hippocampal sclerosis after febrile status epilepticus: The FEBSTAT study. Issue 2 (1st March 2014) - Lewis, Darrell V.; Shinnar, Shlomo; Hesdorffer, Dale C.; Bagiella, Emilia; Bello, Jacqueline A.; Chan, Stephen; Xu, Yuan; MacFall, James; Gomes, William A.; Moshé, Solomon L.; Mathern, Gary W.; Pellock, John M.; et al.
<x xml:space="preserve">Abstract</x> Objective Whether febrile status epilepticus (FSE) produces hippocampal sclerosis (HS) and temporal lobe epilepsy (TLE) has long been debated. Our objective is to determine whether FSE produces acute hippocampal injury that evolves to HS. Methods FEBSTAT and 2 affiliated studies prospectively recruited 226 children aged 1 month to 6 years with FSE and controls with simple febrile seizures. All had acute magnetic resonance imaging (MRI), and follow‐up MRI was obtained approximately 1 year later in the majority. Visual interpretation by 2 neuroradiologists informed only of subject age was augmented by hippocampal volumetrics, analysis of the intrahippocampal distribution of T2 signal, and apparent diffusion coefficients. Results Hippocampal T2 hyperintensity, maximum in Sommer's sector, occurred acutely after FSE in 22 of 226 children in association with increased volume. Follow‐up MRI obtained on 14 of the 22 with acute T2 hyperintensity showed HS in 10 and reduced hippocampal volume in 12. In contrast, follow‐up of 116 children without acute hyperintensity showed abnormal T2 signal in only 1 (following another episode of FSE). Furthermore, compared to controls with simple febrile seizures, FSE subjects with normal acute MRI had abnormally low right to left hippocampal volume ratios, smaller hippocampi initially, and reduced hippocampal growth. Interpretation Hippocampal T2 hyperintensity after FSE represents acute injury often evolving to a radiological appearance of HS after 1 year. Furthermore, impaired growth of normal‐appearing hippocampi after FSE suggests subtle injury even in the absence of T2 hyperintensity. Longer follow‐up is needed to determine the relationship of these findings to TLE. ANN NEUROL 2014;75:178–185